STUDY OF STUDY HABITS, MEMORY AND ASPIRATION LEVEL OF ADOLESCENT STUDENTS OF GENERAL CATEGORY AND BACKWARD CLASS - Sharma, Meenakshi; Sharma, Dr. Manju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The progress of a nation depends on education only. Education helps a person to reach the category of civilized, cultured and capable citizens but it depends on the beliefs and aspirations of a particular society. In India even today the whole society is divided into two parts, first upper class and second lower class. Thus the whole society is confined to only two classes. The lower class has to face financial problems at every step whereas the upper class does not face any financial problems. The government's declaration of equal rights in education only looks like a mirage. The success of any student in school subjects depends on his internal qualities. No matter how many languages ​​or subjects are taught to students at the secondary level, the principal may have the problem of organizing a teacher's seminar every week, a teacher may have the problem of whether his teaching style is satisfactory, a student may have the problem of how he can score more marks in mathematics. The possibility of significant difference at different levels in the aspiration level, study habits and memory level of adolescent students of general category and backward class will be more because the living standard of the students, family background, family values, home environment, all these are capable factors to change the different levels of students.